Treatment of Fibromyalgia Syndrome: Recommendations of Recent Evidence-Based Interdisciplinary Guidelines with Special Emphasis on Complementary and Alternative Therapies. (21st November 2013) - Ablin, Jacob; Fitzcharles, Mary-Ann; Buskila, Dan; Shir, Yoram; Sommer, Claudia; Häuser, Winfried
Abstract : Objective. Current evidence indicates that there is no single ideal treatment for fibromyalgia syndrome (FMS). First choice treatment options remain debatable, especially concerning the importance of complementary and alternative medicine (CAM) treatments. Methods. Three evidence-based interdisciplinary guidelines on FMS in Canada, Germany, and Israel were compared for their first choice and CAM-recommendations. Results. All three guidelines emphasized a patient-tailored approach according to the key symptoms. Aerobic exercise, cognitive behavioral therapy, and multicomponent therapy were first choice treatments. The guidelines differed in the grade of recommendation for drug treatment. Anticonvulsants (gabapentin, pregabalin) and serotonin noradrenaline reuptake inhibitors (duloxetine, milnacipran) were strongly recommended by the Canadian and the Israeli guidelines. These drugs received only a weak recommendation by the German guideline. In consideration of CAM-treatments, acupuncture, hypnosis/guided imagery, and Tai Chi were recommended by the German and Israeli guidelines. The Canadian guidelines did not recommend any CAM therapy. Discussion. Recent evidence-based interdisciplinary guidelines concur on the importance of treatment tailored to the individual patient and further emphasize the need of self-management strategies (exercise, and psychological techniques).